1993
DOI: 10.3109/10428199309148515
|View full text |Cite
|
Sign up to set email alerts
|

Myelomonocytic Antigens are Rarely Expressed on B-Lymphocytic Leukemia Cells

Abstract: In the light of recent observations reporting that B-lymphocytic leukemia (B-CLL) cells may express a variety of myelomonocytic antigens, 28 patients with B-CLL and B-leukemic lymphocytic lymphoma were studied for the presence of these antigens using monoclonal antibodies to detect CD13, CD33, CD15 and CD14. Analysis of immunofluorescence (IF) was carried out by two procedures; one which employed the standard conventional method of gating used in our laboratory for flow cytometry, while the other procedure inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
1

Year Published

1995
1995
2000
2000

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
4
1
Order By: Relevance
“…Some authors reported a high CD14 antigen frequency in their B‐CLL series (Morabito et al , 1987; Molica et al , 1991; Pinto et al , 1992) and a direct correlation between CD14 expression and advanced clinical stages (Molica et al , 1991; Pinto et al , 1992). These results were not confirmed by other studies (Polliack et al , 1993; Tassies et al , 1995). In addition the soluble form of CD14 (sCD14), released from CD14 expressing cells, was reported to be significantly elevated in B‐CLL patients as compared to normal controls (Callea et al , 1996).…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…Some authors reported a high CD14 antigen frequency in their B‐CLL series (Morabito et al , 1987; Molica et al , 1991; Pinto et al , 1992) and a direct correlation between CD14 expression and advanced clinical stages (Molica et al , 1991; Pinto et al , 1992). These results were not confirmed by other studies (Polliack et al , 1993; Tassies et al , 1995). In addition the soluble form of CD14 (sCD14), released from CD14 expressing cells, was reported to be significantly elevated in B‐CLL patients as compared to normal controls (Callea et al , 1996).…”
contrasting
confidence: 99%
“…The aberrant expression of myelomonocytic (MyMo) antigens on acute lymphoblastic leukaemia and multiple myeloma neoplastic cells has been reported and associated with a poor prognosis (Sobol et al , 1987; Wiersma et al , 1991; Grogan et al , 1989). The presence of MyMo antigens has also been described in B‐cell chronic lymphocytic leukaemia (B‐CLL), but the definition of their real frequency and clinical significance is still debated (Woessner et al , 1992; Nakase et al , 1996; Polliack et al , 1993; Tassies et al , 1995). MyMo antigens on B‐CLL cells have been related to the oncogene c‐fos expression and IL‐1 production (Pinto et al , 1987; Morabito et al , 1987).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been controversies regarding the expression of the myelomonocytic antigen CD14. in some studies CD14 has been found to be expressed in a half to two-thirds of CLL cases (75,77,81,82), and it has even been correlated with more advanced stages and poor overall survival (81), these findings have not been confirmed by others (78,80). CD11b expression has been reported to have independent prognostic value for disease progression (77,80), as well as CD11c and CD13 (77).…”
Section: Differential Diagnosis Of Cll With Other Lymphoproliferativementioning
confidence: 99%
“…The differential diagnosis of CLL arises with both primary leukemias and B-cell lymphomas presenting with leukemia. The leukemic phase of a Bcell lymphoma has been recognized for Among the various antigens, the most frequently reported to be expressed in CLL cells are CD11c and CD11b (75)(76)(77)(78)(79)(80), and CD13 (75)(76)(77), while CD33 has been found negative in most of the studies in which this marker has been investigated. There have been controversies regarding the expression of the myelomonocytic antigen CD14.…”
Section: Differential Diagnosis Of Cll With Other Lymphoproliferativementioning
confidence: 99%